A review of using the force/torque sensor in robotics application - Mohd Zaini, Muhammad Zharif; Abdul Rahim, Ruzairi; Abdul Manaf, Mohamad Shukri; Ahmad, Nasarudin (Penerbit UTHM, 2020)
Nowadays, force/torque sensors ubiquitous in the robotics field. Most of the robots on the assembly line use a force/torque sensor in a complex assembly process. A force/torque (F/T) sensor is an electronic device designed to track, detect, record, and manage the rotational and linear forces exerted on it. This force/torque sensor, sometimes known as a multi-axis force/torque transducer, six-axis load cell, or F/T sensor. This sensor plays a vital role in the robotic application as it provides force information to make the system more reliable and precise..